2021
DOI: 10.3389/fchem.2021.682006
|View full text |Cite
|
Sign up to set email alerts
|

A Perovskite-Based Paper Microfluidic Sensor for Haloalkane Assays

Abstract: Detection of haloalkanes is of great industrial and scientific importance because some haloalkanes are found serious biological and atmospheric issues. The development of a flexible, wearable sensing device for haloalkane assays is highly desired. Here, we develop a paper-based microfluidic sensor to achieve low-cost, high-throughput, and convenient detection of haloalkanes using perovskite nanocrystals as a nanoprobe through anion exchanging. We demonstrate that the CsPbX3 (X = Cl, Br, or I) nanocrystals are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The detection/quantification of specialized chemicals, such as CH 3 I, CH 2 Cl 2 , CH 2 Br 2 , benzoyl peroxide, and excessive acid number (AN), via anion exchange mechanisms [ 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ] cannot be regarded as a specific quantification procedure because of its similarity to anion detection. This should be critically investigated to pursue the “state-of-the-art” sensing procedure.…”
Section: Cspbx 3 (X = CL Br and I) And Composites ...mentioning
confidence: 99%
“…The detection/quantification of specialized chemicals, such as CH 3 I, CH 2 Cl 2 , CH 2 Br 2 , benzoyl peroxide, and excessive acid number (AN), via anion exchange mechanisms [ 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ] cannot be regarded as a specific quantification procedure because of its similarity to anion detection. This should be critically investigated to pursue the “state-of-the-art” sensing procedure.…”
Section: Cspbx 3 (X = CL Br and I) And Composites ...mentioning
confidence: 99%
“…Michalska et al demonstrated that the microfluidic-mixing enhanced hole-transporting layers exhibit dramatic reductions in surface energy and an increase in hole mobilities in PSCs, the highest PSCs efficiency up to 15.9% [ 73 ]. Besides, based on the PL spectral shifts of perovskite nanocrystals, using perovskite CsPbX 3 (X = Cl, Br, or I) nanocrystals as a nanoprobe, a paper-based microfluidic sensor through anion exchanging was developed to achieve convenient detection of haloalkanes (CH 2 Cl 2 , CH 2 Br 2 ) [ 24 ].…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%
“…A-site cations can be inorganic or organic ions, such as cesium (Cs), formamidinium (FA), and methylammonium (MA), while B-site cation (Pb 2+ ) could potentially be exchanged by dopant ions (Mn 2+ , Fe 2+ , Ce 3+ , Eu 2+ ) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Therefore, the hybrid organic−inorganic lead halide perovskite, such as CH 3 NH 3 PbX 3 ; and all inorganic lead halide perovskite, such as CsPbX 3 , in the form of nanocrystals, thin films, microcrystals, and bulk single-crystals, show promising properties in LEDs [ 9 , 19 ], lasers [ 20 ], solar cells [ 21 , 22 , 23 ], gas sensors [ 24 ], etc. This review will present the development, progress, and perspectives of halide perovskite synthesis and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Maye et al opened a new halide detection path via the Finkelstein reaction and verified its feasibility in halide exchange. It was the Finkelstein reaction that successively enabled the detections of iodomethane, dichloromethane, , and dibromomethane , based on the halide exchange of CsPbX 3 NPs. Simultaneously, photochemistry provides another potential FAE strategy for perovskite-based halide detection.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, photochemistry provides another potential FAE strategy for perovskite-based halide detection. Son et al and Yang et al demonstrated the photoinduced anion exchange of CsPbX 3 NPs with halomethane under excitation at visible light (405 nm) and Ultraviolet A (365 nm), respectively. Liu et al utilized γ-ray irradiation to promote the halide exchange of bromobenzene and benzyl chloride with CsPbX 3 NPs .…”
Section: Introductionmentioning
confidence: 99%